Access and diversity in South African craft and design: The work of craft intermediaries in Cape Town. (December 2022) - Comunian, Roberta; England, Lauren
Creative intermediaries are increasingly recognised for their role in facilitating the growth and development of creative entrepreneurs and creative and cultural industries. There is also a growing interest in the role of creative and cultural industries in developing economies, for economic development but also cultural engagement and social change. In this article, we bring a Global South perspective to the study of creative intermediaries in the craft sector by exploring how they engage with makers and markets for craft products in Cape Town, South Africa and beyond. Using qualitative interviews with key players from four intermediary organisations working at the community level through to luxury export, we present their different business models and approaches to supporting the development of the craft sector and makers. We reflect on the role they play in addressing inequalities, especially in opportunities to access craft careers and develop sustainable livelihoods for disadvantaged communities. We also consider some of the key challenges these intermediaries face in relation to policy, infrastructure, finance and global competition. The article argues for the value of adopting an ecological perspective in studying the role of craft intermediaries to recognise their role in addressing inequalities in accessing craft careers and the importance of support for makers at different stages in their professional development.